Effective Teachers=Student Achievement : What the Research Says. - Stronge, James H. (Taylor and Francis, 2013)
Research has shown that there is no greater influence on a student's success than the quality of his or her teacher. This book presents the research findings which demonstrate the connection between teacher effectiveness and student achievement. Author James Stronge describes and explains the value-added teacher-assessment research that has emerged in the past decade and demystifies the power and practices of effective teachers.